2020
DOI: 10.1002/slct.202002622
|View full text |Cite
|
Sign up to set email alerts
|

Non‐Invasive, Non‐Enzymatic, Biodegradable and Flexible Sweat Glucose Sensor and Its Electrochemical Studies

Abstract: Glucose oxidase-free polymer composite sensing material, made of polyelectrolytic cellulose derivatives cross-linked by an organic polycarboxylic acid and enhanced by a plasticizer, is reported. The polymer composite is a nontoxic material and is also biodegradable that degrades within 15 days in the soil. The material is extremely flexible and yet resilient in such a way to explicitly fit for application in wearable sensors. Electrochemical analysis of the material for glucose sensing properties with artifici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 37 publications
1
8
0
Order By: Relevance
“…They have covalently immobilized alcohol oxidase on the surface of a graphite electrode which is polymerized with 9-methyl-9Hcarbozole-3-carbohydrazine (MCCH).Alternatively, Debasis Maity et.al., (2018) [20] reported about a layer-by-layer spray coating of multi-walled carbon nanotubes (MWCNT) and PVA on commercially available cotton fabrics and subsequently the ethanol gas sensing properties were determined at room temperature. This work is in continuance with our previous work on the same material for its glucose sensing ability studied and presented in detail [21].…”
Section: Introductionsupporting
confidence: 80%
“…They have covalently immobilized alcohol oxidase on the surface of a graphite electrode which is polymerized with 9-methyl-9Hcarbozole-3-carbohydrazine (MCCH).Alternatively, Debasis Maity et.al., (2018) [20] reported about a layer-by-layer spray coating of multi-walled carbon nanotubes (MWCNT) and PVA on commercially available cotton fabrics and subsequently the ethanol gas sensing properties were determined at room temperature. This work is in continuance with our previous work on the same material for its glucose sensing ability studied and presented in detail [21].…”
Section: Introductionsupporting
confidence: 80%
“…Chronoamperometry (CA) was used to evaluate the peak at −0.1 V. As shown in Figure b, different curves are obtained for different solution concentrations of glucose (0–1 mM) after 60 s. Figure c shows the calibration curve, and the current shows a good linear relationship with the glucose concentration in the range of 0–1 mM, with a correlation coefficient of 0.9793. Based on the slope of the line fitting, the sensitivity is calculated as 3.43 μA mM –1 cm –2 , and the limit of detection is 29.15 μmol L –1 (S/N = 3), which is in the range of human sweat detection in clinical trials . For comparison, Table S1 lists the analytical performance of other Pt-based non-enzymatic glucose electrodes and enzymatic glucose electrodes for sweat glucose detection along with our findings.…”
Section: Results and Discussionmentioning
confidence: 96%
“…Based on the slope of the line fitting, the sensitivity is calculated as 3.43 μA mM −1 cm −2 , and the limit of detection is 29.15 μmol L −1 (S/N = 3), which is in the range of human sweat detection in clinical trials. 35 For comparison, Table S1 lists the analytical performance of other Pt-based non-enzymatic glucose electrodes and enzymatic glucose electrodes for sweat glucose detection along with our findings. It can be observed that a relatively higher sensitivity was obtained on our fabricated sensor.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…[ 126 ]. Among these molecules, glucose in sweat has good correlation with glucose in blood, which has been used in noninvasive electrochemical wearable sensors [ 7 , 103 , 122 , 127 , 128 , 129 ]. However, the normal level of sweat glucose is less than 0.2 mM, which is lower than that in blood serum, with the range of 5.6–6.9 mM.…”
Section: Biomimetic Nanomaterials For Noninvasive Electrochemical Glu...mentioning
confidence: 99%
“…As biomimetic materials, cellulose-based function materials also are used in sweat glucose sensors. For example, Ramadoss et al [ 128 ] reported glucose oxidase-free polymer materials made of polyelectrolytic cellulose derivatives and an organic polycarboxylic acid for glucose sensing properties by electrochemical analysis.…”
Section: Biomimetic Nanomaterials For Noninvasive Electrochemical Glu...mentioning
confidence: 99%